FORMATION OF THE RANGE OF SERVICES - A PRIORITY DIRECTION OF MARKETING ACTIVITY OF A TRAVEL FIRM - KALINICHENKO, Sergiy; VLASENKO, Tetiana; VITKOVSKYI, Yurii; GRIBINYK, Andrey (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The modern system of organized mass tourism is characterized by the fact that end buyers, interacting with producers of primary tourism services, use the services of tour operators, whose activity is to develop a tourism product, its implementation and coordination of interaction between these market parties in the production and consumption of primary tourism services. At the same time, in the conditions of organized tourism in market transactions the object of purchase and sale are not individual primary tourist services (intended to directly meet the needs of tourists), but a complex tourist product as a set of services sold by a tour operator directly or through intermediary structures (travel agencies). Assortment policy as part of the sales policy of the enterprise is primarily in the formation of production and sales program, ie the definition of those types of products (services) that will be sold in certain markets in the planning period. In accordance with the division of the company’s goals into long-term and short-term, the assortment policy is structured into a strategic and operational component. To manage the assortment policy, the company’s management must carefully study and assess the situation in the external environment, identify internal reserves that allow for measures to improve the range. Estimates require current demand in the field of various services, which will effectively manage the range. The management of the range of products or services may be hindered by the internal problems of the organization that have accumulated, so you should analyze the state of affairs, solve problems if they exist and only then implement measures to change the range